Regionalism in the Mekong - Chheang, Vannarith (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The paper discusses the evolution of regionalism in the Mekong region through the lens of liberal institutionalism. It argues regional institutions and mechanisms play a critical role in promoting regional cooperation, especially in socio-economic development and poverty reduction, infrastructure development and connectivity, and environmental cooperation. Regional institutions have contributed significantly to promoting a culture of cooperation, trust building, common interests, and the socialization of norms-based regional cooperation. However, enhancing, synergizing, and harnessing regional institutions are required to better deliver the results of regional institutions. Received 16th December 2016; Revised 20th April 2017; Accepted 25th April 2017